The Effect of Taxonomic Corrections on Phanerozoic Generic Richness Trends in Marine Bivalves with a Discussion on the Clade's Overall History. Issue 1 (27th November 2015) - Mondal, Subhronil; Harries, Peter J.
Abstract: This study uses a comprehensive, revised, and updated global bivalve dataset combining information from two major databases available to study temporal trends in Phanerozoic bivalve richness: the Sepkoski Compendium and the Paleobiology Database. This compilation results in greater taxonomic and stratigraphic coverage than possible with either of the two databases alone. However, there are challenges in directly comparing these two sources due to differences in their taxonomic designations and stratigraphic range information. Moreover, both of these datasets are fraught with a number of taxonomic errors, which can significantly bias the overall richness estimate. Additionally, a substantial number of taxonomic corrections were made before a new Phanerozoic bivalve richness curve was produced. The new generic taxonomic curve is comparable with the trajectory of the Sepkoski's modern fauna and shows rapid and substantial diversification through the Ordovician, followed by a Paleozoic plateau, a Mesozoic high, and Cenozoic diversification after a small reduction in richness associated with the K/Pg extinction. The steep Cenozoic rise documented in the raw richness curve derived from the new dataset is likely real, and reflects the overall robustness and completeness of the bivalve fossil record.